One good dog - Wilson, Susan, 1951- (St. Martin's Press, 2010)
The very definition of a hard-nosed businessman, Adam March has no room in his life for anything but the cold drive to succeed. Not for his social-climbing wife or for his rebellious teenage daughter. then, in an instant, he loses everything, and Adam finds himself alone, unemployed, and reduced to bussing tables in a homeless shelter. Then he meets a dog.